ANALISIS PERANAN RELIGIUSITAS TERHADAP KEPERCAYAAN KEPADA PERBANKAN SYARIAH - DEDI ISKAMTO; YULIHARDI YULIHARDI (Maqdis: Jurnal Kajian Ekonomi Islam, 2017)
The theme of the article is the banks and financial institutions. This study aims to examine the level of influence of Religious on trust to sharia banking. The banking industry is a very sensitive industry with trust. Experience proves that negative issues can undermine trust in the bank. Currently in Indonesia began to develop Syariah Banking but unfortunately the growth of Islamic Banking in Indonesia is not so encouraging growth is very low not comparable with the number of Muslims the majority. Religiusity Indications are associated with dimensions of the dimensions of religious practice, the dimensions of beliefs, the dimensions of religious knowledge, and the dimensions of practice-akhlaq. beliefs are a number of specific beliefs about integrity (trustworthy honesty and ability to keep promises), benevolence (trust and motivation) believed to act in the interests of trusting them, competency (ability of trusted parties to carry out trustworthy needs) and predictability (trustworthiness) consistency of trustworthy party behavior). The value of determinant coefficient (R Square) was obtained at 0.013. This means that the effect of the product on the buying decision is 1.3% while the rest of 98.7% influenced by other variables outside this product variables. The results of hypothesis testing with t test there adannya t count of 1.143 means t count> ttabel = 0.1630 which means Religiusitas significant effect on trust to Bank Syariah.